(untitled) (Journal of Hama University, 2022)
The current research aims to know the degree to which the deans of the faculties at the University of Hama possess administrative competencies in the light of the approach of total quality management from the point of view of the administrative staff and members of the educational staff, and to know the differences in the average responses of the sample members about the degree of possession of the deans of the faculties at the University of Hama of administrative competencies according to the variables of gender and type Work and college type.The research sample consisted of (162) employees and (128) members of the teaching staff who were randomly selected from the faculties of (Education, Economics, Veterinary Medicine, Pharmacy, Dentistry, Arts) at the University of Hama, and the research tool consisted of a questionnaire consisting of (54) items. It is divided into five dimensions: (effective leadership, effective decision-making, strategic planning, participation and teamwork, continuous improvement).The results of the research showed that the degree of possession of administrative competencies by the deans of the faculties at the University of Hama from the point of view of the staff and members of the educational staff was generally large and in each of the axes of the questionnaire, and it was found that there were no differences between the averages of the responses of the sample members about the degree of possession of the deans of the faculties of administrative competencies according to the variable Gender, and there were no differences between the averages of the answers about the degree to which the deans of faculties possessed administrative competencies according to the variable of the type of college, except with regard to the effective leadership axis, in which the differences were in favor of the applied colleges, while there were statistically significant differences according to the variable type of work in favor of members of the teaching staff. The research presented a number of proposals, the most important of which is the need for the university administration to focus on applying the principles of total quality management to improve the university education system in all fields. and benefit from previous global experiences in all countries that have adopted total quality management, which have proven to be highly successful on economic, educational and social growth. and setting scientific standards when selecting deans of faculties at the university based on new specifications related to scientific competencies and expertise related to the concepts of total quality.